Fungal Enzymes Applied to Industrial Processes for Bioethanol Production - Laluce, Cecilia [UNESP]; Igbojionu, Longinus I. [UNESP]; Dussan, Kelly J. [UNESP]; Kumar, S.; Dheeran, P.; Taherzadeh, M.; Khanal, S. (Springer, 2018)
The main biofuels are biodiesel obtained from natural oils and ethanol obtained by fermentation of agricultural residues. Residues of lignocellulosic materials are found worldwide and are one of the most promising renewable substrate for the production of bioenergy. However, the conversion of biomass into biofuel, using fast, cheap and efficient methodologies is the major challenge of biofuel production. The present work intends to cover the composition of lignocellulosic substrates, fungal enzymes, synergism between cellulases and industrial integrated processes for biomass utilization. Concerning applications, fungal enzymes are used in pulp and paper industry, textile, bioethanol, wine and brewery manufacturing, food processing, and animal feed.